NEW TASKS OF INCULTURATION IN A GLOBALIZED INDIA - Joseph, Satish (Asian Horizons, 2011)
Globalization is a multifaceted phenomenon and any effort to define it is outside the scope of this paper. Culture too, is a complex term and there is no effort in this paper to enter into a detailed discussion about it either. However, both globalization and its impact on local cultures is a topic of some very intense debate. Since the topic of this paper is globalization and inculturation it is my intention to address the relationship between the two in the Indian theological context. It is my contention that globalization presents the Indian church an opportunity to renew its own efforts at inculturation.